INTEGRATED REACTOR-SEPARATOR FOR MERCURY DETERMINATION BY USING FIA-CV-AAS TECHNIQUE - Wahyuningjati, Mukti
The ability of mercury compounds as depigmentation material has already know thus many of cosmetic companies using mercury as whitening cream ingredient. Mercury determination in whitening cream by modifying reactor-separator into a single integrated system which have both of the function has been done. This method based on flow injection analysis and cold vapor atomic absorption spectrophotometry technique (FIA-CV-AAS). Parameters which influence the result of measurements has been studied. The developed method has given a good analytical performance. It is proofed with precision value for this method, state as coefficient variant 7.29% (10 ?g.L-1) and 3.59% (50 mg.L-1) and detection limit value are 3.50 ?g.L-1. The linear dynamic range can be gained from concentration 1 ?g.L-1 up to 100 ?g.L-1 with correlation coefficient 0.9968. Accuracy of this method showed by percentage of recovery is more than 95% and the signal increment for 50 ?g.L-1 and 100 ?g.L-1are 2.12 and 3.38 respectively. This method has been applied for determination of trace level concentration of mercury in whitening cream.